The institutional design of European integration: EEC social concerns and development policies between 1957 and 1973 - Renato Raffaele Amoroso (The Journal of European Economic History (JEEH), 2023)
This paper investigates the definition of the European social dimension and the links between development policies and social concerns. The review of a wide literature on the subject confirms the functionalist view that emerged with the Treaties of Rome: measures promoting economic integration and the removal of restrictions on the movement of people, goods, capital and services absorb social measures, which are implemented only as indirect consequences of the progressive market integration. The EIB's intervention in the Mezzogiorno is then analyzed as a case study to evaluate the EEC's approach to the implementation of employment policies in the first fifteen years after the signing of the Treaty of Rome. The research shows that political issues relating to employment and to the integration of individuals into society were mainly entrusted to a technical institution, called upon to operate on the financial market to promote profitable investments in the Community.
Keywords: 330; European integration; contemporary history; EU states; Europäische Integration; Zeitgeschichte; EU-Staaten